Statistics review 9: One-way analysis of variance - Bewick, Viv (BioMed Central, 2004)
This review introduces one-way analysis of variance, which is a method of testing differences between more than two groups or treatments. Multiple comparison procedures and orthogonal contrasts are described as methods for identifying specific differences between pairs of treatments.